Autothermal reforming as a hydrocarbon fuel processing option for PEM fuel cell - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
In this paper, we discuss the results of a preliminary systematic simulation study: the effect of operating parameters on the product distribution and conversion efficiency of high and low molecular weight hydrocarbon mixtures in autothermal reforming (ATR). The HYSYS simulation software has been utilized for the simulations and calculations of the fuel processing reactions. It is desired to produce hydrogen-rich reformate gas with as low as possible CO formation, which requires different combinations of T-ATR, S/C and O/C ratios. Fuel properties only slightly effect the general trends. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: fuel processing; autothermal reforming; fuel cell; hydrocarbon; SYSTEMS